PENYULUHAN KESEHATAN TENTANG GIZI SEIMBANG PADA BALITA DIKELUARGA DALAM PENCEGAHAN STUNTING - Astuti, Tani; Sri Dhamayani; Nurhaida; Widyawati (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
Stunting is a growth disorder in toddlers who do not get enough nutritional intake so that children do not grow according to their age (Amania et al., 2022). Stunting toddlers are chronic nutritional problems caused by many factors such as socio-economic conditions, maternal nutrition during pregnancy, illness in babies and lack of nutritional intake in babies. This Community Service is located in Rugemuk Village, Pantai Labu District, Deli Serdang Regency. The community invited to this activity according to the title of the activity are housewives, young women and men in Rugemuk Village with a total of 20 people. The method chosen is counseling and brainstorming, so that the community in Rugemuk Village, Pantai Labu District, Deli Serdang Regency is healthy, there are no more children with stunting, children grow and develop according to their age. This activity is divided into three stages, namely preparation, implementation, and monitoring stages. The stages that will be implemented are the preparation stage, the Activity Implementation stage and the Evaluation Stage. The implementation of the counseling went effectively.